1994
DOI: 10.1002/eji.1830240206
|View full text |Cite
|
Sign up to set email alerts
|

Murine epidermal Langerhans cells and splenic dendritic cells present tumor‐associated antigens to primed T cells

Abstract: We examined the ability of epidermal Langerhans cells and splenic dendritic cells to present tumor-associated antigens (Ag) to immune T cells. Methylcholanthrene (MCA)-induced subcutaneous fibrosarcomas derived from C57BL/6 mice were used as tumor models. Our data demonstrate that both murine Langerhans cells and splenic dendritic cells have the capacity to present tumor-associated Ag to primed T cells. We found that variously treated tumor preparations (irradiated viable tumor cells, irradiated frozen-stored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 37 publications
1
52
1
Order By: Relevance
“…Presentation of foreign antigens on the surface of DC can be achieved by antigen (peptide) pulsing. [14][15][16][17][18][19][20] According to recent observations, 21 exogenous peptides can enter the MHC class I pathway of antigen presentation and induce cytotoxic T cell responses. Alternatively, presentation of TAA in APC can be achieved by gene transfer techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Presentation of foreign antigens on the surface of DC can be achieved by antigen (peptide) pulsing. [14][15][16][17][18][19][20] According to recent observations, 21 exogenous peptides can enter the MHC class I pathway of antigen presentation and induce cytotoxic T cell responses. Alternatively, presentation of TAA in APC can be achieved by gene transfer techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cohen et al (1994) demonstrated that murine LCs had the capacity to present tumorassociated antigen to primed T cells. In human skin cancer, the number of T6-positive LC per mm2 of section has been reported to decrease significantly (Meissner et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor lysate is other approach for antigen loading of DCs. This approach has been used successfully in many studies [18][19][20][21]. Total antigen loading approaches have the potency to deliver self-antigens and immunosuppressive components, and ultimately reduce antitumor immune responses.…”
Section: Antigen Loading Of Dcsmentioning
confidence: 99%